PENGEMBANGAN BUDAYA DAN IKLIM SEKOLAH DI SMA NEGERI 2 BANDAR LAMPUNG - Ide Lia Marzuki; Sudjarwo Sudjarwo; Irawan Suntoro (9 772338317006)
This research aimed to analyze and describe: (1) Strategies of school culture development; (2) Target of school culture development; (3) Strategies of school climate development; and (4) Target of school climate development in Senior High School 2 Bandar Lampung. The research method used was the phenomenology qualitative research design, which is based on field observation, documentation, and interview. Results of the research were: (1) The strategies of school culture development were establishing good relations, coordinating with surrounding environment, and developing the entrepreneurial program; (2) Target of the development was by applying information and communication technologies, modernization of teaching facilities; (3) Strategies of school climate development were always innovating, have standards to achieve satisfactory results, as well as giving the reward; (4) Target of school climate development, were increase the level comfort of school, maximize the learning process, interpersonal relationships between students, teachers, and parents, cooperation with environmental institution.Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan: (1) Strategi pengembangan budaya sekolah; (2) Sasaran pengembangan budaya sekolah; (3) Strategi pengembangan iklim sekolah; dan (4) Sasaran pengembangan iklim sekolah di SMA 2 Bandar Lampung. Penelitian ini menggunakan desain penelitian kualitatif fenomenologi, yang didasarkan pada observasi lapangan, dokumentasi, dan wawancara. Hasil dari penelitian ini adalah: (1) Strategi pengembangan budaya sekolah dengan menjalin hubungan baik, berkoordinasi dengan lingkungan sekitarnya, dan mengembangkan program kewirausahaan; (2) Sasaran dari pengembangan adalah dengan menerapkan teknologi informasi dan komunikasi, modernisasi fasilitas pengajaran; (3) Strategi pengembangan iklim sekolah dengan selalu berinovasi, memiliki standar untuk mencapai hasil yang memuaskan, serta memberikan hadiah; (4) Target pengembangan iklim sekolah adalah dengan meningkatkan tingkat kenyamanan disekolah, memaksimalkan proses belajar, hubungan interpersonal antara siswa, guru, dan orang tua, bekerja sama dengan lembaga disekitar sekolah.Kata kunci: budaya sekolah, iklim sekolah, pengembangan